Impact of harbour activities on local air quality: A review. (February 2020) - Sorte, Sandra; Rodrigues, Vera; Borrego, Carlos; Monteiro, Alexandra
Abstract: Several harbour activities cause negative environmental impacts in the harbours' surrounding areas, namely the degradation of air quality. This paper intends to comprehensively review the status of the air quality measured in harbour areas. The published studies show a limited number of available air quality monitoring data in harbours areas, mostly located in Europe (71%). Measured concentrations of the main air pollutants were compiled and intercompared, for different countries worldwide allowing a large spatial representativeness. The higher NO2 and PM10 concentrations were found in Europe - ranging between 12 and 107 μg/m 3 and 2–50 μg/m 3, respectively, while the higher concentrations of PM2.5 were found in Asia (25–70 μg/m 3 ). In addition, the lower levels of SO2 monitored in recent years suggest that current mitigation strategies adopted across Europe were very efficient in promoting the reduction of SO2 concentrations. Part of the reviewed studies also estimated the contributions from ship emissions to PM concentration through the application of source apportionment methods, with an average of 5–15%. In some specific harbour areas in Asia, ships can contribute up to 7–26% to the local fine particulate matter concentrations. This review confirms that emissions from the maritime transport sector should be considered as a significant source of particulate matter in harbour areas, since this pollutant concentrations are frequently exceeding the established standard legal limit values. Therefore, the results from this review boost the implementation of mitigation measures, aiming to reduce, in particular, particulate matter emissions. Graphical abstract: Image 1 Highlights: Maritime sector emissions are a main source of air pollution over harbour areas. The highest concentrations of NO2 and PM10 are found in European harbours. Recent mitigation strategies in the European territory have proved their efficiency. PMF is the most common method for source-apportionment among all case studies. Abstract : A review was performed focused on air quality over harbour areas, concluding that shipping activities have a significant contribution to PM and NO2 emissions: the highest concentrations of NO2 and PM10 are found in European harbours, ranging between 12 and 107 μg/m 3 and 2–50 μg/m 3, respectively, while the highest PM2.5 concentrations were found in Asia, ranging from 25 to 70 μg/m 3 .